ANALYSIS OF ELECTRONIC MONEY USAGE BEHAVIOR ON THE MILENNIAL GENERATION IN INDONESIA - Leonardus Prakoso (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
The Covid-19 pandemic that began in 2019 forced people to be able to carry out all aspects of life without interacting directly, including in saving and transacting activities. Under these conditions, electronic money is present as the main tool to accommodate people's needs. This study tries to identify the factors that influence the behavior of millennials in Indonesia regarding the use of electronic money. The model used in the study adopted the UTAUT and E-SQ models. The results of the study show that the millennial generation's intention to use electronic money in Indonesia is significantly influenced by application reliability, customer service, and electronic money application design.